2023
DOI: 10.1186/s12877-023-04055-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors that maintain physical function or increase frailty using the Kihon checklist among community-dwelling older adults: a six-year longitudinal study in Agano, Japan

Abstract: Background A significant increase in the older adult population in Japan will significantly increase healthcare costs. This study aimed to examine the risk factors contributing to robustness transitioning to frailty in older residents. Methods Participants were aged 70 in 2016 and 76 in 2022. Participants were evaluated using the Kihon Checklist (KCL). Results Participants for this longitudinal study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To assess the construct validity of the JFS-C, we examined its correlations with assessment of frailty (the Frail scale), ADL(Barthel Index), and HRQoL(SF-36). The original version of the questionnaire study showed a moderate correlation between JFS and the Kihon Checklist and Locomo-5 ( 15 ), which is a questionnaire measuring elderly mobility function The Kihon Checklist is a questionnaire that reflects frailty status ( 33 ). Locomo-5 is a questionnaire that reflects elderly physical function, which is similar to our research design.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the construct validity of the JFS-C, we examined its correlations with assessment of frailty (the Frail scale), ADL(Barthel Index), and HRQoL(SF-36). The original version of the questionnaire study showed a moderate correlation between JFS and the Kihon Checklist and Locomo-5 ( 15 ), which is a questionnaire measuring elderly mobility function The Kihon Checklist is a questionnaire that reflects frailty status ( 33 ). Locomo-5 is a questionnaire that reflects elderly physical function, which is similar to our research design.…”
Section: Discussionmentioning
confidence: 99%